Numerical methods for the inverse dynamics simulation of underactuated mechanical systems - Yang, Yinping (Schriftenreihe des Instituts für Mechanik, Karlsruher Institut für Technologie, 2017)
The present work deals with the inverse dynamics simulation of underactuated multibody systems. In particular, the study focuses on solving trajectory tracking control problems of differentially flat underactuated systems. The use of servo constraints provides an approach to formulate trajectory tracking control problems of underacutated systems, which are also called underactuated servo constraint problems.